Implementation of Flood Disaster Mitigation Strategy in Nagari Taram, Lima puluh Kota Regency - Yusran, Rahmadani; Alhadi, Zikri; Basri, Zahari; Sabri, Rika (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study aims to analyze the implementation of flood disaster mitigation strategies in Nagari Taram, Limapuluh Kota Regency. This study uses a qualitative method with a descriptive approach. They were collecting data using interviews, observation, and documentation study. The research informants were several heads of fields, section heads in the Regional Disaster Management Agency of Fifty Cities Distr2ict. The results showed that the implementation of disaster mitigation by the local government had been carried out in the form of the normalization of Batang Sinamar, brojong development along the Batang Sinamar watershed. However, the mitigation that has been implemented has not succeeded in reducing the risk and impact of flooding on the community in Nagari Taram. This study argues that local governments need to pay attention to regional characteristics in implementing flood disaster mitigation before carrying out river normalization because the area's characteristics affect the carrying capacity and carrying capacity of the river.